Do fiscal decentralization and income inequality affect the size of the shadow economy? A panel data analysis for OECD countries. Issue 8 (4th May 2018) - Berger, Wolfram; Salotti, Simone; Sardà, Jordi
ABSTRACT: In this article, we study fiscal decentralization and inequality as driving forces of the shadow economy in advanced economies. Our empirical analysis suggests that a reduction in income inequality will contain the shadow economy, whereas expenditure and tax decentralization do not significantly impact it. As decentralization is generally believed to increase government efficiency, this result is indicative of already highly efficient public administrations. Our results further indicate that redistributive policies positively affect the size of the shadow economy, whereas the tax burden does not have any discernible effect on the shadow economy in our sample.